2010
DOI: 10.1177/0363546510371371
|View full text |Cite
|
Sign up to set email alerts
|

Midterm Follow-up of Opening-Wedge High Tibial Osteotomy

Abstract: Medial opening-wedge high tibial osteotomy produces good results in the midterm. After the osteotomy, a more normal appearing weightbearing pattern with double peaks was seen. The adduction moment significantly decreased, resulting in less contact pressure through the medial degenerative compartment of the knee. The authors recommend medial opening-wedge high tibial osteotomy for young patients with varus alignment and medial compartment arthritis to allow this patient population to remain highly active and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
77
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 52 publications
12
77
1
3
Order By: Relevance
“…Several authors have reported good results with allograft [3][4][5], despite the fact that it is associated with a higher failure rate when compared to autograft [16]. The augmentation with calcium phosphate ceramics has been also investigated [12,13], while the experience with xenograft is scanty [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have reported good results with allograft [3][4][5], despite the fact that it is associated with a higher failure rate when compared to autograft [16]. The augmentation with calcium phosphate ceramics has been also investigated [12,13], while the experience with xenograft is scanty [6].…”
Section: Discussionmentioning
confidence: 99%
“…Several strategies have been proposed as alternatives to autologous bone graft, including allograft [3][4][5], xenograft [6], hydroxyapatite [7][8][9], acrylic cement [10,11] and calcium phosphate [12,13] wedges.…”
Section: Introductionmentioning
confidence: 99%
“…Valgus-producing medial open-wedge high tibial osteotomy (owHTO) is an established procedure for the treatment fixation devices have been developed for owHTO, such as an inlay system [21], short spacer plates with or without locking screws [4,6,16,32,43,48,60], and locking screw plate fixators with [25] and without a spacer [13,18,19,36,40,45,49,65].…”
Section: Introductionmentioning
confidence: 99%
“…However, substantial discordance also has been observed between the severity of patient's symptoms, and radiographic evidence of degenerative changes in knee OA (including JS narrowing). [7,19,27,62] Likewise, peak knee adduction moment during gait has been correlated with medial knee OA pain [36,63], varus alignment [17], mechanical axis [52], load distribution [5,36], compartmental bone mineral content [37], and radiographic evidence of disease progression [4,50,66]. However, conflicting reports exist related to knee adduction moment.…”
Section: Discussionmentioning
confidence: 99%